(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Rwanda is a developing country located in the middle of Central Africa, which has faced multiple economic challenges since its independence not too long ago. A civil war in the country left it in a vulnerable and weak position. However, the country’s resilience and commitment led to it turning its destiny around. This paper discusses the various measures taken by Rwanda that allowed it to achieve economic progress, one of the highest GDP growth rates in Africa, and reduce poverty in a short time span. Policies and reforms centered around trade, tourism, and social development, along with support from the multilateral institutions, are identified to be among the key drivers of Rwanda’s progress.